2000
DOI: 10.1023/a:1002793728087
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hypovitaminosis A is associated with exocrine pancreatic insufficiency in cystic fibrosis. Peripheral retinal dysfunction is an early finding of vitamin A deficiency. We evaluated serum retinol and zinc as well as visual adaptation in 41 patients with cystic fibrosis, receiving generous pancreatic enzyme and micronutrient supplementation. Forty-one normal individuals matched for age and sex served as controls. Peripheral retinal function was measured by clinical electroretinography using an Electrophysiologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Overall, our PI and PS groups were broadly similar to Fulton et al's data from healthy children, indicating no clear effects of cystic fibrosis in rod scotopic, maximal and cone photopic electrical responses. This also agrees with the findings of Tsinopoulos et al, who reported no difference between a supplemented PI population and a healthy comparison control group [10].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Overall, our PI and PS groups were broadly similar to Fulton et al's data from healthy children, indicating no clear effects of cystic fibrosis in rod scotopic, maximal and cone photopic electrical responses. This also agrees with the findings of Tsinopoulos et al, who reported no difference between a supplemented PI population and a healthy comparison control group [10].…”
Section: Discussionsupporting
confidence: 93%
“…A lack of statistically significant difference between the ERG measures of PI and PS groups tested here indicates that nutrient supplementation levels in the PI group are adequate to allow approximately comparable retinal function in the groups with and without malabsorption. Previous work indicates that flash ERGs are normal in PI cystic fibrosis patients [10]. Our findings are in general agreement with this, and show that, within a CF population, flash ERGs are not obviously different between PI and PS groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations